The endogenous Coxiella burnetii plasmid encodes a functional toxin–antitoxin system. Issue 6 (28th November 2022) - Wachter, Shaun; Cockrell, Diane C.; Miller, Heather E.; Virtaneva, Kimmo; Kanakabandi, Kishore; Darwitz, Benjamin; Heinzen, Robert A.; Beare, Paul A.
Abstract: Coxiella burnetii is the causative agent of Q fever. All C. burnetii isolates encode either an autonomously replicating plasmid (QpH1, QpDG, QpRS, or QpDV) or QpRS‐like chromosomally integrated plasmid sequences. The role of the ORFs present in these sequences is unknown. Here, the role of the ORFs encoded on QpH1 was investigated. Using a new C. burnetii shuttle vector (pB‐TyrB‐QpH1ori), we cured the C. burnetii Nine Mile Phase II strain of QpH1. The ΔQpH1 strain grew normally in axenic media but had a significant growth defect in Vero cells, indicating QpH1 was important for C. burnetii virulence. We developed an inducible CRISPR interference system to examine the role of individual QpH1 plasmid genes. CRISPRi of cbuA0027 resulted in significant growth defects in axenic media and THP‐1 cells. The cbuA0028 / cbuA0027 operon encodes CBUA0028 (ToxP) and CBUA0027 (AntitoxP), which are homologous to the HigB2 toxin and HigA2 antitoxin, respectively, from Vibrio cholerae . Consistent with toxin–antitoxin systems, overexpression of toxP resulted in a severe intracellular growth defect that was rescued by co‐expression of antitoxP . ToxP inhibited protein translation. AntitoxP bound the toxP promoter (P toxP ) and ToxP, with the resulting complex binding also P toxP . In summary, our data indicate that C. burnetii maintains an autonomously replicating plasmid because of a plasmid‐based toxin–antitoxin system. Abstract : Coxiella burnetii is an obligate intracellular bacterium and causative agent of Q fever. Here we report that the C. burnetii genome encodes 11 toxin–antitoxin systems, which is highly unusual for intracellular bacteria, and that one TA system is encoded on the large endogenous plasmid found in almost all C. burnetii isolates. This TA system has a "noncanonical" toxin first gene orientation and acts at the RNA polymerase to cleave incoming mRNAs to prevent protein translation.